2016
DOI: 10.4187/respcare.04857
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a β-Agonist/Airway Clearance Protocol in a Pediatric ICU

Abstract: BACKGROUND: Respiratory therapist (RT)-driven protocols have been in use for over 30 years.Protocols have been reported to decrease unnecessary or harmful therapy, health-care costs, and hospital stay. This study represents the evaluation of an original respiratory care protocol in the pediatric ICU at Arkansas Children's Hospital for ␤-agonist and airway clearance interventions where one did not exist. METHODS: This project was composed of 2 parts: a survey administered to RTs and licensed independent practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The routine processes lie somewhere in the middle. Using the broom metaphor, and based upon the results of the study by Lowe and colleagues, 13 ␤-agonist and airway clearance treatments are clearly standards (ie, the handle of the broom).…”
Section: See the Original Study On Page 259mentioning
confidence: 99%
See 2 more Smart Citations
“…The routine processes lie somewhere in the middle. Using the broom metaphor, and based upon the results of the study by Lowe and colleagues, 13 ␤-agonist and airway clearance treatments are clearly standards (ie, the handle of the broom).…”
Section: See the Original Study On Page 259mentioning
confidence: 99%
“…[6][7][8][9][10] Reducing practice variation through standard care protocols and clinical pathways has been shown to reduce the costs associated with care, shorten the duration of mechanical ventilation, and reduce the stay in the PICU in a number of studies reported in this journal. 11,12 In this issue of RESPIRATORY CARE, Lowe et al 13 report the findings of a retrospective analysis of a quality improvement intervention in their PICU whose primary aim was to standardize the use of ␤-agonists and airway clearance for critically ill children with acute respiratory failure. 13 Physician-directed orders (pre-intervention group) were replaced by a standardized, respiratory therapistdriven protocol (post-intervention group).…”
mentioning
confidence: 99%
See 1 more Smart Citation